Measurement of the production of a W boson in association with a charm quark in pp collisions at √s = 7TeV with the ATLAS detector - Santos, S. P. Amor dos (2014)
The production of a W boson in association with a single charm quark is studied using 4.6 fb-1 of pp collision data at √s = 7TeV collected with the ATLAS detector at the Large Hadron Collider. In events in which a W boson decays to an electron or muon, the charm quark is tagged either by its semileptonic decay to a muon or by the presence of a charmed meson. The integrated and differential cross sections as a function of the pseudorapidity of the lepton from the W-boson decay are measured. Results are compared to the predictions of next-to-leading-order QCD calculations obtained from various parton distribution function parameterisations. The ratio of the strange-to-down sea-quark distributions is determined to be 0.96+ - 0 0.30 at Q2 = 1.9 GeV, which supports the hypothesis of an SU(3)-symmetric composition of the light-quark sea. Additionally the cross-section ratio σ(W+ + c)/σ(W- +c) is compared to the predictions obtained using parton distribution function parameterisations with different assumptions about the s–s quark asymmetry.